1978
DOI: 10.1002/1097-0142(197803)41:3<827::aid-cncr2820410307>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Halothane, surgery, immunosuppression and artificial pulmonary metastases

Abstract: C57B1/6 mice were given intravenous tumor cells on day O. Mice were then given either a brief exposure to halothane anesthesia or given halothane and then underwent a hind limb amputation. Immune testing was done at varying time intervals and correlated with the development of artificial pulmonary metastases. The effects of a single 15 minute exposure to halothane on the immune system are probably short-lived and no effect on cell-mediated cytotoxicity was seen on day 7, nor was an increase in pulmonary metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
4

Year Published

1979
1979
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 9 publications
2
15
0
4
Order By: Relevance
“…Numerous studies (Kurosawa S, 2008) have shown that recently, alongside with immune suppression caused by surgical stress, anaesthetics and analgesic agents commonly used in surgery and in intensive care may directly affect the functions of immune-competent cells. Since the reactivation of HHV-6 and HHV-7 viral infection is more pronounced in patients of general anaesthesia group, our data are consistent with the previous studies that general anaesthesia does not suppress the surgical stress response, thus exacerbating postoperative immunosupression (Stevenson, 1990), (Lundy, 1978). Immunosupression is the main cause of the reactivation of HHV-6 and HHV-7 viral infection.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies (Kurosawa S, 2008) have shown that recently, alongside with immune suppression caused by surgical stress, anaesthetics and analgesic agents commonly used in surgery and in intensive care may directly affect the functions of immune-competent cells. Since the reactivation of HHV-6 and HHV-7 viral infection is more pronounced in patients of general anaesthesia group, our data are consistent with the previous studies that general anaesthesia does not suppress the surgical stress response, thus exacerbating postoperative immunosupression (Stevenson, 1990), (Lundy, 1978). Immunosupression is the main cause of the reactivation of HHV-6 and HHV-7 viral infection.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported in the literature that surgery may cause immunosuppression, 24,25 consistent with an increase in the rate of metastases. However, following surgery in this model, the rates of metastases in the lung and groin were lower and higher, respectively, compared with untreated control but these differences were not statistically significant.…”
Section: The Response Of Distant Metastasis To Local Pd-bpheid-pdt Ofmentioning
confidence: 71%
“…However, his observations are well aligned with studies from more than four decades ago, when the association between volatile anesthetics and neoplasm progression was first observed. Lundy et al proposed that the combination of halothane, surgery and immunosuppression increased pulmonary metastases in mice inoculated with tumor cells [4]. Shapiro et al found that lung tumor progression was accelerated in mouse models when exposed to halothane and nitrous oxide [5].…”
Section: The Effect Of General Anesthesia On Cancer Recurrencementioning
confidence: 99%